2001
DOI: 10.1128/aem.67.5.2088-2094.2001
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Laccase Activity in Rhizoctonia solani by Antagonistic Pseudomonas fluorescens Strains and a Range of Chemical Treatments

Abstract: Fungi often produce the phenoloxidase enzyme laccase during interactions with other organisms, an observation relevant to the development of biocontrols. By incorporating the laccase substrate 2,2-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) into agar, we analyzed laccase induction in the plant-pathogenic fungus Rhizoctonia solani when paired against isolates of the soil bacterium Pseudomonas fluorescens. Substantial induction of R. solani laccase was seen only in pairings with strains of P. fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
79
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 30 publications
3
79
0
1
Order By: Relevance
“…Although fungi have mechanisms for metal tolerance [12], the activity of their extracellular enzymes has been shown to be modulated during the metal exposures in liquid cultures. Copper increases the extracellular laccase in different filamentous fungi [13][14][15]. It is also known that Cu induces the laccase transcription in Trametes versicolor [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although fungi have mechanisms for metal tolerance [12], the activity of their extracellular enzymes has been shown to be modulated during the metal exposures in liquid cultures. Copper increases the extracellular laccase in different filamentous fungi [13][14][15]. It is also known that Cu induces the laccase transcription in Trametes versicolor [16].…”
Section: Introductionmentioning
confidence: 99%
“…One study on the plant-pathogenic fun- As mentioned above, fungal laccase may be involved in the adaptive response to oxidative stress. However, the hypothesis that laccase plays an important role in defense against oxidative stress is mainly based on the phenomenon that laccase activity can be induced by various oxidative stress factors (2,12,16,20,(32)(33)(34). To our knowledge, there is little direct evidence supporting the involvement of laccase in the defense against oxidative stress.…”
mentioning
confidence: 85%
“…One study on the plant-pathogenic fun-gus Rhizoctonia solani has revealed that copper, paraquat, and alcohol treatments, which are known to cause oxidative stress by promoting the formation of free radicals, can induce laccase activity and increase the level of lipid peroxidation. A straightforward link between oxidative stress and laccase induction was found in the case of paraquat treatment (20). A genetic study on another plant-pathogenic fungus, Fusarium oxysporum, has also suggested that laccase may have a role in protection against oxidative stress.…”
mentioning
confidence: 96%
“…A qualitative laccase assay in dermatophytes was modified from Srinivasan et al (1995) and Crowe & Olsson (2001) by evaluating the oxidation of 2,29-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS; Sigma). The assay buffer used was a mixture of 0.1 M boric acid, 0.1 M acetic acid and 0.1 M phosphoric acid (Britton-Robinson buffer) adjusted to pH 5.0 with NaOH (Wahleithner et al, 1996).…”
mentioning
confidence: 99%